A little give in rubber - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Rubber production in Côte dIvoire continues to experience a modest annual growth of 7% to 10%. Following a trend that started five years ago, the country Africas largest producer produced 120,000 t in 2000. The 2001 harvest is nearing...